The implicit theories in the practice of teaching - Fernández Heredia, Blanca de la Luz (Consorcio de Universidades Mexicanas A.C., 2018)
The practice of teaching is influenced by multiple factors that are present in the teaching action. Monereo states that a teacher is many teachers in one, this thought according to the vision of the flexible professional that is currently sought, with the ability to adapt to different groups of students, but without betraying their conceptions and convictions regarding the way that is taught and learned. Therefore, when the teacher thinks about what he is going to do in class, he reflects the reality of what is inside his mental structure. In this way, the link between the teaching practice and the implicit theories is stronger and more important than would be expected, so that the objective of this work is to carry out a reflexive analysis on the way in which the implicit theories influence and determine the teaching practice carried out by teachers in the classroom. Taking the teacher into account as a reflective professional, an aspect that should be encouraged in the training offered to teachers. To lead him to the theoretical proposal of the implicit theories and how they relate to the practice of his teaching.